2017
DOI: 10.1001/jamainternmed.2017.2657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Intervention to Reduce Hospitalizations From Nursing Homes

Abstract: IMPORTANCE Medicare payment initiatives are spurring efforts to reduce potentially avoidable hospitalizations. OBJECTIVE To determine whether training and support for implementation of a nursing home (NH) quality improvement program (Interventions to Reduce Acute Care Transfers [INTERACT]) reduced hospital admissions and emergency department (ED) visits. DESIGN, SETTING, AND PARTICIPANTS This analysis compared changes in hospitalization and ED visit rates between the preintervention and postintervention period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
188
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(210 citation statements)
references
References 27 publications
14
188
2
6
Order By: Relevance
“…For example, a recent trial of INTERACT, an intervention designed to reduce hospitalisations of nursing home residents, showed no apparent benefit 30. The authors contend this null result could reflect the challenges of implementing a complex, resource-intensive intervention in the nursing home setting, something noted in pre-trial studies where drop-out of nursing homes was a concern 31.…”
mentioning
confidence: 99%
“…For example, a recent trial of INTERACT, an intervention designed to reduce hospitalisations of nursing home residents, showed no apparent benefit 30. The authors contend this null result could reflect the challenges of implementing a complex, resource-intensive intervention in the nursing home setting, something noted in pre-trial studies where drop-out of nursing homes was a concern 31.…”
mentioning
confidence: 99%
“…Because no effects were seen in the intention‐to‐treat analyses, analyses were conducted on a subset of 85 of these SNFs that reported no use of INTERACT before the trial was initiated (33 intervention, 52 control), with the hypotheses that these SNFs would be more likely to show an effect. These analyses demonstrated a significant effect on 1 of the 5 outcomes (PAHs using CMS definitions), but this finding did not remain robust to a Bonferroni correction …”
mentioning
confidence: 99%
“…Finally, although we measured the impact of the program for 15 months, the long‐term effect could differ. An important future research project would be to randomly assign GPs and nursing homes to a program such as was implemented in Denmark, especially because Kane et al found less promising results with INTERACT when homes were randomly assigned vs when they volunteered.…”
Section: Discussionmentioning
confidence: 99%
“…Ouslander et al and Ingber et al found that nursing homes that volunteered to implement the program experienced reductions in hospitalizations, with reductions in preventable admissions also occurring in the latter study † . In a recent study where 85 nursing homes were randomly assigned to receive training and implementation support for INTERACT, however, there was no impact on hospitalizations, readmissions, or preventable hospitalizations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation